ความชุกและจีโนไทป์ของเชื้อไวรัสตับอักเสบซีในประเทศไทย - ศรัณย์ธร สุนันท์ชัยการ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
Hepatitis C virus is a major cause of acute and chronic hepatitis worldwide. At least 170 million world populations have been infected with this virus. Hepatitis C virus can be classified into 6 major genotypes based on phylogenetic analysis of the genomic sequences. Some genotypes (genotype 1, 2 and 3) are endemic worldwide, while others may be restricted to distinct geographical regions. The 3 major genotypes found in Thailand are genotype 1, 3 and 6. Genotype 3 is the most prevalence genotype in the country. In this study 5825 serum samples of people of 4 provinces from the North (Chiangrai), North-east (Udornthani), Southern (Nakornsrithammaraj) and Centre (Chonburi) of Thailand were collected and 125 (2.15%) samples were positive for anti-HCV by ELISA. To investigate HCV-RNA, all of the Anti-HCV positive samples were 58 (58.00%) positive performed by RT-PCR based on 5 UTR. Among RNA positive samples, there were 50 (86.21%) core RT-PCR positive samples. These core-PCR positive samples were sequenced and classified into genotype 1a; 3 (6.66%), 1b; 12 (26.66%), 2a; 1 (2.22%), 2c;1 (2.22%), 3a; 23 (51.11%), 3b; 1 (2.22%) and genotype 6 variants; 4 (8.89%). In case of NS5B RT-PCR, there were 54 (93.11%) positive samples and divided into genotype 1a; 3 (18.75%) 1b; 4 (25.00%), 3a; 6 (37.50%), 3b; 1 (6.25%) and genotype 6 variants; 2 (12.50%). We found that there are 5 irrelevant genotyping results between core and NS5B region. Those results need further investigation. The study revealed an anti-HCV seroprevalence rate representing the whole nation s perspective. In addition, this information might play important roles in public health surveillance and prevention.